New records of the spotfin burrfish Chilomycterus reticulatus (Linnaeus, 1758) along the Italian coasts - FALAUTANO, MANUELA; LIVI, SILVIA; TIRALONGO, FRANCESCO; AZZURRO, ERNESTO; GRECH, DANIELE; MASALA, CLAUDIO; CASTRIOTA, LUCA (Mediterranean Marine Science, 2025)
Here we report two new records of the spotfin burrfish, Chilomycterus reticulatus, in the Mediterranean Sea, detected through a public awareness campaign designed to inform citizens about the presence of hazardous alien fish species. The first specimen was recorded by a professional fisherman in January 2023, stranded along the coast of Lazio, central Tyrrhenian Sea, Italy. The specimen was collected and identified through morphological and molecular methods as C. reticulatus. Moreover, its gut content was analyzed showing mollusc fragments, some of which belonged to Bolinus brandaris. A second specimen of C. cf. reticulatus was observed and filmed in Sardinia on 29 June 2024 in the framework of another citizen science initiative.